2021
DOI: 10.1097/bsd.0000000000001205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity Severity on Achieving a Minimum Clinically Important Difference Following Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: Objective: The objective of this study was to determine the impact of obesity on postoperative outcomes and minimum clinically important difference (MCID) achievement following minimally invasive transforaminal lumbar interbody fusion (MIS TLIF).Summary of Background Data: Obesity is a proven risk factor for poorer outcomes in MIS TLIF patients. However, few studies have investigated the impact of body mass index (BMI) on achievement of a MCID for Patient-Reported Outcome Measurement Information System Physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Kern Singh and his team found that hospitalized patients, patients with milder preoperative lower extremity pain and patients with shorter preoperative symptom duration may achieve better clinical outcomes ( 15 , 16 , 17 ). On the other hand, patients with severe preoperative disability, significant low back pain, low mental functioning, and higher degrees of obesity (BMI ≥ 30) tend to have worse clinical outcomes ( 18 , 19 , 20 , 21 ). ASA (American Society of Anesthesiologists) classification, severity of comorbidities, time to surgery (TTS), and duration of symptoms (DOS) had no significant impact on patient clinical outcomes ( 22 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kern Singh and his team found that hospitalized patients, patients with milder preoperative lower extremity pain and patients with shorter preoperative symptom duration may achieve better clinical outcomes ( 15 , 16 , 17 ). On the other hand, patients with severe preoperative disability, significant low back pain, low mental functioning, and higher degrees of obesity (BMI ≥ 30) tend to have worse clinical outcomes ( 18 , 19 , 20 , 21 ). ASA (American Society of Anesthesiologists) classification, severity of comorbidities, time to surgery (TTS), and duration of symptoms (DOS) had no significant impact on patient clinical outcomes ( 22 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%